Sensation seeking and smoking behaviors among adolescents in the Republic of Korea. (June 2015) - Hwang, Heejin; Park, Sunhee
Abstract: Objective: This study aimed to explore the relationship between the four components of sensation seeking (i.e., disinhibition, thrill and adventure seeking, experience seeking, and boredom susceptibility) and three types of smoking behavior (i.e., non-smoking, experimental smoking, and current smoking) among high school students in the Republic of Korea. Methods: Multivariate multinomial logistic regression analysis was performed using two models. In Model 1, the four subscales of sensation seeking were used as covariates, and in Model 2, other control factors (i.e., characteristics related to demographics, individuals, family, school, and friends) were added to Model 1 in order to adjust for their effects. Results: In Model 1, the impact of disinhibition on experimental smoking and current smoking was statistically significant. In Model 2, the influence of disinhibition on both of these smoking behaviors remained statistically significant after controlling for all the other covariates. Also, the effect of thrill and adventure seeking on experimental smoking was statistically significant. The two statistically significant subscales of sensation seeking were positively associated with the risk of smoking behaviors. Conclusions: According to extant literature and current research, sensation seeking, particularly disinhibition, is strongly associated with smoking among youth. Therefore, sensation seeking should be measured among adolescents to identify those who are at greater risk of smoking and to develop more effective intervention strategies in order to curb the smoking epidemic among youth. Highlights: Little is known about the link between sensation seeking and smoking in Asian youth. The effects of DIS and TAS on smoking behaviors were strong in Korean adolescents. DIS was the factor most strongly associated with the smoking behaviors.